Retrospective study assessing range of motion of two prosthetic models in the early postoperative period. Issue 5 (September 2018) - Villalba, J.; Balaguer-Castro, M.; Marcano-Fernández, F. A.; Torner, P.
Abstract : Background: The aim of this study was to investigate range of motion (ROM) gained by mobile-bearing (MB) and cruciate-retaining (CR) knee prostheses in the early postoperative period with a view to determining which of the two accomplishes its goal sooner, assuming no significant differences in long-term outcomes. Methods: A retrospective cohort study was performed comparing outcomes in the early postoperative period. Ninety-two CR designs were compared with 100 MB designs, over a follow-up period of 1 yr. Knees were evaluated at discharge and at 1, 3, and 6 mo, as well as at 1-year postoperatively using ROM and the Knee Society Score (KSS) as the main variables. Results: Both groups were equivalent in terms of gender, age, body mass index, ROM, and KSS at baseline. Results showed that ROM values improved significantly faster in the MB group at 1 and 3 mo after discharge as compared to the CR group, even though differences between both groups tended to even out with time. Both groups showed a significant improvement in KSS values 6 mo after discharge with significant differences in the final values, although the improvement was more substantial in the MB group. Conclusions: The MB group showed a faster recovery after total knee arthroplasty, as compared with the CR group, even though both groups tended to converge over time. The results obtained could allow a reduction in rehabilitation time and an early return to normal activities.